RANCANG BANGUN ALAT BANTU PERAKITAN DAN PENGELASAN KURSI LABORATORIUM (LAB STOOL) - Alang Sunding; Ulia Ridhani; Imron Burhan (P3M Politeknik Negeri Indramayu, 2018)
The quality of mass produced lab stools are determined based on the similarity of shape andsize of the labs stools produced. Assembly work is done by two technicians for 55 minuteswithout using assembly tools (Fixture). Based on this data, it can be inferred that in termsof working time assembly process is considered too long or inefficient in terms of time.Based on the amount of labor it is still not efficient or the productivity is still low, so theremust be innovations made to speed up the assembly time. in addition to low productivity,without assembly tools and welding the product is not similiar because there is a change ofshape after welding process. It means the quality of the product is not good. Businesscompetition in the field of metal furniture manufacture is growing so that producers have tothink of methods to improve productivity, quality and speed up production time. To increaseproductivity, it is necessary to assemble and fix the parts to be assembled to eliminateunwanted movement due to the welding distortion. The use of fixtures in the assemblyprocess can be done by one person with an average processing time of 25 minutes.